Role of methanotrophic communities in atmospheric methane oxidation in paddy soils - Zheng, Yan; Cai, Yuanfeng; Jia, Zhongjun (Frontiers in Microbiology, 2024)
Wetland systems are known methane (CH4) sources. However, flooded rice fields are periodically drained. The paddy soils can absorb atmospheric CH4 during the dry seasons due to high-affinity methane-oxidizing bacteria (methanotroph). Atmospheric CH4 uptake can be induced during the low-affinity oxidation of high-concentration CH4 in paddy soils. Multiple interacting factors control atmospheric CH4 uptake in soil ecosystems. Broader biogeographical data are required to refine our understanding of the biotic and abiotic factors related to atmospheric CH4 uptake in paddy soils. Thus, here, we aimed to assess the high-affinity CH4 oxidation activity and explored the community composition of active atmospheric methanotrophs in nine geographically distinct Chinese paddy soils. Our findings demonstrated that high-affinity oxidation of 1.86 parts per million by volume (ppmv) CH4 was quickly induced after 10,000 ppmv high-concentration CH4 consumption by conventional methanotrophs. The ratios of 16S rRNA to rRNA genes (rDNA) for type II methanotrophs were higher than those for type I methanotrophs in all acid-neutral soils (excluding the alkaline soil) with high-affinity CH4 oxidation activity. Both the 16S rRNA:rDNA ratios of type II methanotrophs and the abundance of 13C-labeled type II methanotrophs positively correlated with high-affinity CH4 oxidation activity. Soil abiotic factors can regulate methanotrophic community composition and atmospheric CH4 uptake in paddy soils. High-affinity methane oxidation activity, as well as the abundance of type II methanotroph, negatively correlated with soil pH, while they positively correlated with soil nutrient availability (soil organic carbon, total nitrogen, and ammonium-nitrogen). Our results indicate the importance of type II methanotrophs and abiotic factors in atmospheric CH4 uptake in paddy soils. Our findings offer a broader biogeographical perspective on atmospheric CH4 uptake in paddy soils. This provides evidence that periodically drained paddy fields can serve as the dry-season CH4 sink. This study is anticipated to help in determining and devising greenhouse gas mitigation strategies through effective farm management in paddy fields.